Neurotoxicity of high dose intrathecal neostigmine - Bayar, M.K.; Cetin, H.; Onal, A.; Gezen, M.; Erhan, O.L. (My University, 1998)
Our study has been designed to investigate possible histopatological changes in the central nervous system of experimental animals following the administration of intrathecal neostigmine. We have included 18 New Zealand type rabbits weighing between 3250-3750 g into our study. The subjects were anaesthetized with IM 3 mg/kg xyzlazine and 40 mg/kg ketamine. Intrathecal neostigmine was administered to group I, II and III with 50, 100, and 150 ?g/kg of respective doses by accessing the dura from the lumbar zone. The animals were sacrified after 24, 48 and 72 hours under deep anaesthesia with glutheraldehyde perfusion. The central nervous systems of the subjects were removed and specimens were obtained from the lumbar, thoracal and cervical zones. These specimens were dyed in hemotoxilen eozin and Kluwer-Barrea and examined under light microscopy. The histopatological examination showed a decrease in the Nissl bodies in one subject in group II in the specimens removed after 48 hours. No other histopatological deficiencies were detected. While dose dependent tremors were observed in subjects, group III animals demonstrated respiratory and cardiac arrest. It has been concluded that high dose intrathecal neostigmine administration should be performed carefully keeping in mind that adverse effects may occur.
Yuksek doz intratekal neostigminin norotoksisitesi
Keywords: Intrathecal anaesthesia; Neostigmine; Neurotoxicity